Size Exclusion Chromatography: An Indispensable Tool for the Isolation of Monodisperse Gold Nanomolecules - Sakthivel, Naga Arjun; Jupally, Vijay Reddy; Eswaramoorthy, Senthil Kumar; Wijesinghe, Kalpani Hirunika; Nimmala, Praneeth Reddy; Kumara, Chanaka; Rambukwella, Milan; Jones, Tanya; Dass, Amala (Analytical chemistry (Washington), 2021)
Highly monodisperse and pure samples of atomically precise gold nanomolecules (AuNMs) are essential to understand their properties and to develop applications using them. Unfortunately, the synthetic protocols that yield a single-sized nanomolecule in a single-step reaction are unavailable. Instead, we observe a polydisperse product with a mixture of core sizes. This product requires post-synthetic reactions and separation techniques to isolate pure nanomolecules. Solvent fractionation based on the varying solubility of different sizes serves well to a certain extent in isolating pure compounds. It becomes tedious and offers less control while separating AuNMs that are very similar in size. Here, we report the versatile and the indispensable nature of using size exclusion chromatography (SEC) as a tool for separating nanomolecules and nanoparticles. We have demonstrated the following: (1) the ease of separation offered by SEC over solvent fractionation; (2) the separation of a wider size range (∼5–200 kDa or ∼1–3 nm) and larger-scale separation (20–100 mg per load); (3) the separation of closely sized AuNMs, demonstrated by purifying Au137(SR)56 from a mixture of Au329(SR)84, Au144(SR)60, Au137(SR)56, and Au130(SR)50, which could not be achieved using solvent fractionation; (4) the separation of AuNMs protected by different thiolate ligands (aliphatic, aromatic, and bulky); and (5) the separation can be improved by increasing the column length. Mass spectrometry was used for analyzing the SEC fractions.